ANALISIS KANDUNGAN ZAT PENGAWET FORMALIN PADA TERASI YANG DIPERDAGANGKAN DI PASAR TRADISIONAL KOTA KENDARI - Fadli, Rian Al (Jurnal Sains dan Teknologi Pangan, 2016)
Condiment is a product preserved small fish or rebon that have been processed through fermentation, grinding or pulverization, and drying. In addition, the shelf life of shrimp is still relatively minimal. Thus, alternatives are always in use by the community in increasing the shelf life of shrimp, which add substance pengaet formaldehyde in order shrimp paste stored and sold last much longer. To find out how big the formalin used to preserve paste the analytical methods are used mainly qualitative and quantitative test. This study aims to determine the formaldehyde content in the paste traded in Traditional Markets Kendari. The average percentage of formaldehyde in each market respectively Markets Baruga A and B (100; 120)mg/kg, Long Market A and B (160; 160)mg/kg, Market Anduonohu ​​A and B (120; 140)mg/kg and Market Wet A and B (120; 104)mg/kg. The results of the study provide information that samples taken from the traditional market town kendari 8 positive for formaldehyde. Keywords: Formalin, Shrimp Paste, Kualitaif Test, Quantitatif Test.